The Legal Responsibility Resulting from Deteriorating Road Conditions in the Kingdom of Saudi Arabia - Al-Shaibani, Majed N. (International journal of criminal justice sciences, 2024)
There is a long debate to ascertain the legal responsibility that arises because of hazardous roadways in Saudi Arabia. Islamic faith promotes the pursuit of excellence and regards dishonesty as one of the gravest transgressions in Islamic law. Hence, the primary objective of this study was to ascertain the legal repercussions placed on the party accountable for the deficiencies in constructing or upkeeping deteriorated roadways, both from a civil law and religious standpoint. Islamic faith mandates that individuals strictly follow the rules of road preservation and maintenance. It primarily focuses on identifying the parties responsible for road deterioration. Furthermore, it classifies the various forms of road damage and outlines the procedures and legislation implemented by the Saudi Courts to provide compensation to injured parties due to poor road conditions. This study outlines the precise methods and procedures followed by Saudi courts to handle compensation claims. This study utilized a qualitative approach, focusing on data collection and analysis, to achieve its objectives. Key findings emphasize the need for authorities to properly assess road damage risks involving all relevant stakeholders. It also highlights the importance of identifying the party responsible for substandard road construction when contractors fail to meet specified standards. This study recommends that Saudi lawmakers develop clear laws and regulations to address these issues.